Crisis of Muslim migrants' identity in Abdulrazak Gurnah’s novel Memory of Departure - Mohsen, Hamoud Yahya Ahmed; Alosman, Abdulrahman; Al-Bakr, Fahd Ibrahim (University of Malaya, 2025)
This paper examines the crisis of Muslim migrant identity in Abdulrazak Gurnah’s novel entitled Memory of Departure (1987), highlighting the psychological, cultural, and existential struggles faced by African Muslim migrants in postcolonial contexts. Through a cultural and postcolonial lens, the study investigates how Gurnah articulates the crisis of identity of Muslim protagonists who find themselves dislocated from their African homelands and alienated within their host society, particularly Britain. The novel captures the sense of exile and displacement rooted in political oppression, economic instability, and post-independence disillusionment that force many African Muslims to seek refuge abroad. However, instead of stability, they encounter cultural marginalization, religious dissonance, and identity confusion Gurnah’s narrative reflects a complex negotiation between memory and identity, as the protagonist reimagines Africa not as a place of return but as a site of trauma and loss. These reflections underscore the emotional toll of migration and the difficulty of constructing a coherent self amid fractured cultural landscapes. The study argues that Memory of Departure presents a powerful critique of both African political realities and Western cultural hegemonies, framing the crisis of Muslim migrant identity within a broader diasporic consciousness